Trimen’s false tiger moth, Agoma trimenii (Lepidoptera: Agaristidae) : biology and potential control options - Morris, Courtney Anne (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.